The Contacts of Martin Ludwig Rhesa with Lithuanian Song Collectors Working in the Country - Citavičiūtė, Liucija (Knygotyra, 2019)
The personal archive of Martin Ludwig Rhesa (1776–1840), who had gathered and prepared the first known collection of Lithuanian songs, contains the letters of two of Rhesa’s respondents from the country – of Enrikas Budrius (1783–1852), teacher of the Brėdausių estate school, and of Wilhelm Ernst Beerbohm (1786–1865), chief inspector of littoral fishing. The archive itself was taken to Königsberg after the Second World War and is today stored in the Manuscript Department of the Wroblewski Library of the Lithuanian Academy of Sciences. Budrius wrote his letters during 1818–1827 and contained in them songs that he had heard in the Pilupėnų area. He was one of the contributors who had captured the melodies of the songs, which he would hear performed during Lithuanian feasts or other types of gatherings. Budrius has sent more than 20 songs, yet only one – Žvirblytis – was eventually included in the printed collection; Rhesa himself gave a copy to Budrius. The letters contain discussions on Lithuanian songs and their melodies; we see some talks regarding a project to write the Lithuanian history using the Lithuanian language, and there are some personal motives present in the letter as well. Beerbohm, the other respondent, corresponded with Rhesa during the former’s last years, during 1835–1839; these two men were from the same region and had met several times in Königsberg. Beerbohm’s letters contain ample supplementary content – songs and regional vocabularies, fishermen phraseology, Lithuanian names of littoral plants and sea fish, etc. The drawings and schemes of vytinė trading boats and ice fishing, complemented with Lithuanian terms, are the first Lithuanian visual and explanatory dictionaries. Some of these words are not included in any of the Lithuanian dictionaries – not now, and not even then. Each of the respondents have authored a poem dedicated to Rhesa. Budrius wrote his poem in Lithuanian. Four Beerbohm’s letters and three written by Budrius are extant. Judging by the circumstances referred to in the letters, it is possible to state that Rhesa wrote at least four or five letters to these individuals.